Local and Global Myths in Shakespearean Performance (Reproducing Shakespeare, 2018)
This collection of scholarly essays offers a new understanding of local and global myths that have been constructed around Shakespeare in theatre, cinema, and television from the nineteenth century to the present. Drawing on a definition of myth as a powerful ideological narrative, Local and Global Myths in Shakespearean Performance examines historical, political, and cultural conditions of Shakespearean performances in Europe, Asia, and North and South America. The first part of this volume offers a theoretical introduction to Shakespeare as myth from a twenty-first century perspective. The second part critically evaluates myths of linguistic transcendence, authenticity, and universality within broader European, neo-liberal, and post-colonial contexts. The study of local identities and global icons in the third part uncovers dynamic relationships between regional, national, and transnational myths of Shakespeare. The fourth part revises persistent narratives concerning a political potential of Shakespeare's plays in communist and post-communist countries. Finally, part five explores the influence of commercial and popular culture on Shakespeare myths. Michael Dobson's Afterword concludes the volume by locating Shakespeare within classical mythology and contemporary concerns. .